Development of a fuzzy-based telecommuting capability assessment tool via mobile application - Gamara, Rex Paolo C. (Animo Repository, 2023)
By early 2020, COVID-19 has caused a global pandemic which led to an enormous number of challenges worldwide in various sectors. The Philippine government has implemented multiple quarantine guidelines and travel restrictions to ensure the people’s health and safety. However, the International Labour Organization (ILO) projected an initial economic and labor market disruption affecting 11 million workers, or about 25% of the Philippine workforce, due to the pandemic. Therefore, the government, thru the concerned agencies continues to encourage employers to implement alternative work plans such as a work-from-home (WFH) operation in compliance with the established regulations in line with existing laws and policies both for the public (government) and the private sector. In line with the telecommuting concept, various research has already been performed, however, some were regarded inconclusive and require further study. Hence, in this research, a mobile application was developed to evaluate the employee’s telecommuting capability assessment using a Fuzzy-based model programmed via Google Apps Script using JavaScript. The mobile application utilizes AppSheet as the main development environment and Google Sheets as the main backend. The developed mobile application is able to provide capacity evaluation utilizing the four key input variables, which are also reasonably characterized for potential telecommuting cost evaluation. The study could serve as a significant resource for future research pertaining to telecommuting. To further enhance the system, more parameters may be considered and examined. Ultimately, the study's deployment of telecommuting suggests that the mobile application tool is highly beneficial in terms of HR metrics.